PENGHIMPUNAN DANA ZAKAT MELALUI BANK KONVENSIONAL DALAM PERSPEKTIF FIKIH MUAMALAH - Muhammad Zuhirsyan; Nurlinda Nurlinda; Irwan Musriza; Supaino Supaino (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2023)
This paper aims to analyze the problem of collecting zakat funds in the management of contemporary zakat funds through conventional banks from the perspective of muamalah fiqh. This research is a field study with data collection methods in research using observation observations with data analysis used using descriptive analysis based on the analysis of muamalah fiqh principles regarding contemporary zakat fundraising. The results of the study show that empowering Islamic banking in collecting and even managing it is a necessity that zakat managers must provide Islamic bank accounts in an effort to collect zakat funds, this is an effort to ensure that all transactions carried out are in accordance with Islamic sharia coredor. However, conventional banking accounts are also needed in the field, so sharia banking accounts must be a top priority. Keywords: Zakat, Conventional Banks, Jurisprudence, Muamalah